Acinetobacter baumannii Resistance to Sulbactam/Durlobactam: A Systematic Review - Luigi Principe; Stefano Di Bella; Jacopo Conti; Mariagrazia Perilli; Alessandra Piccirilli; Cristina Mussini; Giuliana Decorti (Antibiotics, 2022)
Infections caused by carbapenem-resistant Acinetobacter baumannii (CRAB) have limited therapeutic options. Sulbactam-durlobactam is a combination of two βlactamase inhibitors with activity against CRAB under phase 3 clinical investigation. We performed a systematic review on in vitro studies reporting A. baumannii resistances against sulbactam/durlobactam. We considered “resistant” species to be those with MIC ≥ 8 mg/L. Ten studies were included in the review (9754 tested isolates). Overall, 2.3% of A. baumannii were resistant to sulbactam/durlobactam, and this percentage rose to 3.4% among CRAB subgroups and to 3.7% among colistin-resistant strains. Resistance was 100% among metallo β-lactamase-producing strains. Overall, in 12.5% of cases, sulbactam/durlobactam resistance was associated with the production of NDM-1, in 31.7% of cases with the substitutions in the PBP3 determinants, and in the remaining cases the resistance mechanism was unknown. In conclusion, A. baumannii resistance towards sulbactam/durlobactam is limited, except for MBL-producing strains.